2009
DOI: 10.5194/angeo-27-427-2009
|View full text |Cite
|
Sign up to set email alerts
|

Topside measurements at Jicamarca during solar minimum

Abstract: Abstract. Long-pulse topside radar data acquired at Jicamarca and processed using full-profile analysis are compared to data processed using more conventional, range-gated approaches and with analytic and computational models. The salient features of the topside observations include a dramatic increase in the T e /T i temperature ratio above the F peak at dawn and a local minimum in the topside plasma temperature in the afternoon. The hydrogen ion fraction was found to exhibit hyperbolic tangent-shaped profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 38 publications
(41 reference statements)
3
37
0
Order By: Relevance
“…This approach is intermediate between gated analysis (e.g., Hysell et al, 2009) and full-profile analysis (e.g., Holt et al, 1992;Hysell et al, 2008) because of we use the forward model to calculate the lag product matrices (e.g., Hysell et al, 2009) which are then compared with measurements but assume that only IS signal power changes with height. Our simulations showed that involving of even smoothed…”
Section: Appendix Amentioning
confidence: 99%
“…This approach is intermediate between gated analysis (e.g., Hysell et al, 2009) and full-profile analysis (e.g., Holt et al, 1992;Hysell et al, 2008) because of we use the forward model to calculate the lag product matrices (e.g., Hysell et al, 2009) which are then compared with measurements but assume that only IS signal power changes with height. Our simulations showed that involving of even smoothed…”
Section: Appendix Amentioning
confidence: 99%
“…Using these direct observations or indirect derivations of upper transition height, some scientific researches have been done. It was found that upper transition height can have significant variations with solar activity, season, local time, and location (Gonzá lez and Sulzer, 1996;Hysell et al, 2009;Kutiev et al, 1980;MacPherson et al, 1998;Truhlík et al, 2005;West et al, 1997). Meanwhile, empirical models of the upper transition height have been constructed (e.g., Kutiev et al, 1994;Kutiev and Marinov, 2007; Marinov et al, 2004;Trísková et al, 2003) and they have potential application to improve the representation of the ion composition in the ionosphere empirical models such as IRI (Bilitza and Reinisch, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Truhlík et al (1998) compared the O + /H + transition height with that of O + /(H + +He + ) and found that the latter usually is lower by 100 km than the former. Upper transition height is an important parameter for either ionosphere modeling or ionosphere-plasmasphere coupling study (Bilitza and Reinisch, 2007;Gonzá lez and Sulzer, 1996;Hysell et al, 2009;MacPherson et al, 1998;Marinov et al, 2004;Webb et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISR at Arecibo Observatory, located near the town of Arecibo, Puerto Rico, has a very large aperture, which makes it uniquely suited for sensitive investigations of ionospheric state parameters (Erickson and Swartz, 1994;Sulzer and Gonzá lez, 1996;Gonzá lez and Sulzer, 1996). A recent study by Hysell et al (2009) shows that Jicamarca has excellent sensitivity for topside studies; they also provide a good description of the behavior of the equatorial topside ionosphere during solar minimum. Parameters such as electron density, ion composition, and ion and electron temperatures can be measured routinely (Isham et al, 2000), and at lower heights, collision frequencies between ions and neutral constituents (Fentzke et al, 2011) as well as the number density of the neutral atmosphere can also be estimated.…”
Section: Introductionmentioning
confidence: 96%